(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigates the governance of natural resources to promote socio-economic and people-centred development in Nigeria. The paper relied on secondary sources of data, focusing on the three main variables: conflict, politics and power. Nigeria is endowed with abundant natural resources, which accounts for about 65% of total tax revenue, driven mostly by an increase in export earnings from the oil and gas sector. Most resource-related conflicts are implicated by the inequitable distribution of benefits accruing to resources. The State and elite, in alliance with foreign corporations, enjoy the benefits of the exploited resource. Host-communities face the debilitating negative environmental impacts and the discrepancy between indigenous traditional laws and state laws that define ownership of natural resources in a federal but unitary state has led to controversial relations among states in Nigeria. The paper took an extensive look at the politics of natural resource extraction and governance in Nigeria and explored the themes through which the causative relationship between natural resources and conflicts can be differentiated. It noticed the political economy of natural resources as embedded within the broader global power relations. The paper concludes that regulation must be anchored to elements of good governance, especially democracy, rule of law, transparency and accountability, as well as efficient and equitable management of resource revenues.